Pink Noises : Women on Electronic Music and Sound - Rodgers, Tara, 1973- (Book collections on Project MUSE., 2010)
A collection of twenty-four interviews with women in electronic music and sound cultures, including club and radio DJs, remixers, composers, improvisers, instrument builders, and performance artists.